VDACs: An Outlook on Biochemical Regulation and Function in Animal and Plant Systems - Ravi, Barkha; Kanwar, Poonam; Sanyal, Sibaji K.; Bheri, Malathi; Pandey, Girdhar K. (Frontiers in Physiology, 2021)
The voltage-dependent anion channels (VDACs) are the most abundant proteins present on the outer mitochondrial membrane. They serve a myriad of functions ranging from energy and metabolite exchange to highly debatable roles in apoptosis. Their role in molecular transport puts them on the centre stage as communicators between cytoplasmic and mitochondrial signaling events. Beyond their general role as interchangeable pores, members of this family may exhibit specific functions. Even after nearly five decades of their discovery, their role in plant systems is still a new and rapidly emerging field. The information on biochemical regulation of VDACs is limited. Various interacting proteins and post-translational modifications (PTMs) modulate VDAC functions, amongst those, phosphorylation is quite noticeable. In this review, we tried to give a glimpse of the recent advancements in the biochemical/interactional regulation of plant VDACs. We also cover a critical analysis on the importance of post-translational modifications in the functional regulation of VDACs. Besides, the review also encompasses numerous studies which can identify VDACs as a connecting link between Ca2+ and ROS signaling in special reference to the plant systems.